Classical Pathway Complement Activation on Human Endothelial Cells - Yin, Wei (2006)
Endothelial cells regulate vascular integrity and express complement binding proteins including gC1qR/p33 (gC1qR), which recognize C1q, a subunit of the first component of the classical complement pathway. Experiments were performed to investigate classical complement pathway activation on resting endothelial cells and endothelial cells exposed to shear stress. C1q deposition and C4 activation (C4d) were demonstrated by solid phase ELISA and flow cytometry on human microvascular and umbilical vein endothelial cells after exposure to serum or plasma. C4d deposition was accompanied by downstream complement activation including C3b and C5b-9 deposition. C4 activation failed to occur in C1q depleted serum, but was not affected by Factor B depleted serum, confirming classical complement pathway activation. Moreover, C4 activation occurred following exposure of endothelial cells to purified C1 and C4, in the absence of other plasma proteins, and in the absence of detectable cell surface IgG and IgM. Shear stress (18 dynes/cm(2)) increased C1q (n=9, p<0.05) and C4d (n=9, p<0.05) deposition approximately 2-fold, and enhanced endothelial cell gC1qR expression (n=7, p<0.05). Treatment of endothelial cells with anti gC1qR monoclonal antibody F(ab’)(2) fragments reduced C4d deposition by approximately 20% (n=5, p<0.05). These data demonstrate direct classical complement pathway activation on endothelial cells. gC1qR appears to play a minor but definable role, whereas cell surface IgG or IgM are not required.